A 2D copper(I) metal-organic framework: Synthesis, structure and luminescence sensing for cupric, ferric, chromate and TNP. (April 2020) - Qian, Lin-Lu; Wang, Zhi-Xiang; Ding, Jian-Gang; Tian, Hai-Xin; Li, Ke; Li, Bao-Long; Li, Hai-Yan
Abstract: A multi-responsive Cu-MOF {[Cu I 2 (ttpa)2 ][Cu II (bptc)]3H2 ODMF}n (13H 2 ODMF ) was synthesized using hydrothermal method (ttpa = tris(4-(1, 2, 4-triazol-1-yl)phenyl)amine, H4 bptc = 3, 3′, 4, 4′-biphenyltetracarboxylic acid), and characterized by elemental analysis, IR spectra, single-crystal and powder X-ray diffraction analysis, TGA, luminescence and XPS. 1 exhibits the (3, 3)-connected 6 3 -hcb topologic cationic networks [Cu I 2 (ttpa)2 ]n encapsulated the [Cu II 2 (bptc)2 ] 4- dimeric anions. 1 is a good luminescence sensor for multi-detection, sensitivity and recyclability of Cu 2+, Fe 3+, Cr2 O7 2−, CrO4 2− and TNP. 1 shows the highest Ksv 2.460 × 10 5  M −1 for detection of Cu 2+ of MOFs sensors and the lowest detection limit 0.062 μM (3.9 ppb) for MOFs sensors, which is obvious lower than the permissible concentrations 2.0 μM (1.3 ppm) and 3.1 μM (2.0 ppm) in drinking water determined by the US EPA and WHO. 1 exhibits the high Ksv 5.350 × 10 4  M −1 for detection of Cr2 O7 2− and 5.311 × 10 4  M −1 for CrO4 2−, and the low detection limit 0.058 μM (13.0 ppb) for Cr2 O7 2− and 0.070 μM (8.1 ppb) for CrO4 2−, which is below the acceptable limit for the drinking water standard (total chromium 100 ppb by the US EPA). 1 also exhibits the high Ksv 6.646 × 10 4  M −1 and the low detection limit 0.22 μM (50 ppb) for detection of TNP. 1 exhibits high photocatalytic efficiency for degradation of methylene blue under visible light irradiation. Graphical abstract: A Cu-MOF was synthesized and characterized by elemental analysis, IR spectra, UV–vis spectra, single-crystal and powder X-ray diffraction analysis, TGA, XPS, and luminescence. 1 shows 2D cationic networks [Cu I 2 (ttpa)2 ]n encapsulated the [Cu II 2 (bptc)2 ] 4- dimeric anions. 1 is a good luminescence sensor for multi-detection, sensitivity and recyclability of Cu 2+, Fe 3+, Cr2 O7 2−, CrO4 2− and TNP. 1 shows the highest Ksv 2.460 × 10 5  M −1 for detection of Cu 2+ of MOFs sensors and the lowest detection limit 0.062 μM (3.9 ppb). Image 1 Highlights: IR spectra, UV–vis spectra, X-ray diffraction analysis, TGA, XPS, and luminescence. Luminescence sensor for detection of Cu 2+, Fe 3+, Cr2 O7 2−, CrO4 2− and TNP. The highest Ksv 2.460 × 10 5  M −1 and the lowest detection limit 0.062 μM for detection of Cu 2+ for MOFs sensors. The high Ksv 5.350 × 10 4  M −1 for detection of Cr2 O7 2− and 5.311 × 10 4  M −1 for CrO4 2− . The high Ksv 6.646 × 10 4  M −1 and low detection 0.22 μM for detection of TNP.